RESEPSI SASTRA NOVEL SARAH KARYA ‘ABBAS MAHMUD AL-‘AQQAD - Uki Sukiman (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
Sarah’s novel is a unique masterpiece of an author dubbed as Imlaq al-'Arab (The Giant), ‘Abbas Mahmud al-‘Aqqad. This novel is unique because it is the only of his work written in the form of novels among his works. It's pretty awesome because al-'Aqqad has written about 83 books in various fields of science and 10 anthologies of poetries. The presence of this novel provokes some responses of various groups of litterateurs, writers, and readers, either a positive or a negative response, particularly when it is associated with al-‘Aqqad’s side of life as well as the condition of society in his time of life. To review this novel, the author uses the Reception Theory in Literature. The theory emphasizes the reader's reception of a literary text as an important factor in the interpretation of literature. In fact, the reader as interpreter presents diversity of meaning in accordance with the Horizon of Expectations as Hans Robert Jauss said. In addition, the diversity of reader reception is also based on characters of literature itself. It always presents 'open plek' according to Walfgang Iser. It will be filled and solidified differently by the readers. The method used is the Critical Approach that aims to discuss the reception developments of review, criticism, commentary, analysis, or other forms of research such as graduating papers, theses, and dissertations. Reader’s reception toward the novel of Sarah published in1964 up to 2005 shows on three receptions feature. First, the novel is supposed as a novel presenting the women's psychological analysis. Second, Sa>rah novel is as an autobiographical novel that describes the author's love story. Third, Sarah novel is a realist novel depicting the reality of class conflict and describing the attitude of women leaders and scholars of Egypt in facing of modernization.